Flattening which curve? Property-price gradients in New South Wales during the COVID-19 pandemic - Nicholas Sheard (Regional Studies, Regional Science)
This paper tests how the patterns of residential property values in the Australian state New South Wales changed during the COVID-19 pandemic. Between 2019 and 2021, property values became relatively high in medium-sized towns and cities, suggesting those locations became more attractive. In its capital and largest city Sydney, the premium on proximity to the central business district (CBD), where employment is heavily concentrated, decreased after 2019 and that decrease persisted beyond the end of pandemic measures. The premium in Sydney on proximity to the beach has increased, but on a trajectory consistent with an existing trend. The decreased premium on proximity to the CBD since 2019 appears to have initially been related to the value of access via public transport, but then also to the value of access by car. The findings suggest shifts in regional development and urban form that could have implications for how cities are planned and developed.